Evaluasi Penilaian Kinerja Guru dan Sistem Pembelajaran (Indo-MathEdu Intellectuals Journal, 2024)
Evaluation of the performance of educators is an important process in assessing the effectiveness of the education system in achieving educational goals that have been set. Assessment of educator performance not only focuses on academic aspects, but also involves various other aspects, including social aspects, skills, and student character. In this study, will be discussed some key aspects in the evaluation of the performance of educators from the definition of performance evaluation of educators, basic concepts of performance evaluation, evaluation objectives, ways and tools of performance evaluation, formative and summative evaluation, as well as the involvement of teachers in the evaluation process, at the conclusion of this discussion, the authors get the results that the evaluation of the performance of educators can be done through a variety of methods and evaluation tools, such as standardized tests, formative assessment, observation, and interviews. The purpose of this evaluation is to identify strengths and weaknesses in the education system, as well as provide relevant information for improvement. Evaluation of educator performance is an important tool in improving the quality of education. By engaging various stakeholders and using appropriate evaluation methods, the education system can continue to evolve and provide better education for future generations